Понятие и признаки организованной преступности - Исмаилова, З (SCIENCE and SOCIETY, 2018)
The struggle with organized crime is one of the most important and problem objects today. The effectiveness of struggle against organized crime may be achieved by the way of reinforcemental large scale of preventive measures of impact to social dangerous or new produced groups. It means in its tunn the totality of measures on settling the struggle against organized and tactical crime. Бул мақала Өзбекстан Республикасы Олий Мажлиси жанындағы мәмлекетлик емес, коммерциялық емес шөлкемлерди ҳәм пуқаралық жәмийетиниң басқа да институтларын қоллап-қуўатлаў Жәмийетлик фонды тәрепинен қаржыландырылған «Ҳәрекетлер стратегиясын жасларымыз билиўи керек!» жойбар шеңберинде жәрияланды.
Keywords: organized crime; organized group; criminal organization; organized armed group; criminal law